Common Neural Basis of Motor Sequence Learning and Word Recognition and Its Relation With Individual Differences in Reading Skill. (2nd January 2019) - Hung, Yi-Hui; Frost, Stephen J.; Molfese, Peter; Malins, Jeffrey G.; Landi, Nicole; Mencl, W. Einar; Rueckl, Jay G.; Bogaerts, Louisa; Pugh, Kenneth R.
ABSTRACT: To investigate the neural basis of a common statistical learning mechanism involved in motor sequence learning and decoding, we recorded brain activation from participants during a serial reaction time (SRT) task and a word reading task using functional magnetic resonance imaging. In the SRT task, a manual response was made depending on the location of a visual cue, and the order of the locations was either fixed or random. In the word reading task, visual words were passively presented. In the inferior frontal gyrus pars triangularis (IFGpTr) and the insula, differences in activation between the ordered and random condition in the SRT task and activation to printed words in the word reading task were correlated with the participants' decoding ability. We speculate that extraction of statistically predictable patterns in the IFGpTr and insula contributes to both motor sequence learning and orthographic learning, and therefore predicts individual differences in decoding skill.